Laser microdissection-based microproteomics of formalin-fixed and paraffin-embedded (FFPE) tissues - Longuespée, Rémi; Baiwir, Dominique; Mazzucchelli, Gabriel; Smargiasso, Nicolas; De Pauw, Edwin (Laser capture microdissection, 2018)
Laser microdissection-based proteomics on formalin-fixed and paraffin-embedded tissues is usually performed from relatively large tissue areas or pools of multiple tissue pieces. However, several molecular pathology studies require working on very limited amounts of tissue. This is for example the case when very early cancer lesions have to be handled. Hereby, we present a method for the processing of very small pieces of formalin-fixed and paraffin-embedded tissues for proteomic purposes. This approach is designed in order to avoid sample loss during technical processing and to optimize the digestion of tissue areas containing as little as 2700 cells.